2016
DOI: 10.1021/acs.jpcc.6b03964
|View full text |Cite
|
Sign up to set email alerts
|

Thickness Dependence of Carrier Mobility and the Interface Trap Free Energy Investigated by Impedance Spectroscopy in Organic Semiconductors

Abstract: The authors report the hole mobilities of organic semiconductors (OSCs): N,N′-di-[(1-naphthalenyl)-N,N′-diphenyl]-1,1′-biphenyl)-4,4′-diamine and N,N′-bis (3-methyl- phenyl)-N,N′-diphenylbenzidine in various thick films (50–800 nm) by impedance spectroscopy. The experimental results show that the mobility increases with the increase of thickness. After extrapolating the area of electric field by fitting the P–F equation, we find that the thickness ratio is the primary cause for the change of the carrier mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…[14,15] For instance, it has previously been shown that thin-film transistors (TFTs) based on different semiconductor materials exhibit a universal trait: the charge carrier mobility reduces with lowering channel thickness below a critical dimension. [16][17][18][19][20][21][22][23] This phenomenon applies to numerous established technologies including silicongermanium transistors, [16] GaAs/AlGaAs quantum wells, [17] as well as emerging semiconductor technologies including 2D materials (e.g., MoS 2 ), [18] organic semiconductors, [19][20][21] and metal oxide semiconductors. [22][23][24] Traditionally, the The dependence of charge carrier mobility on semiconductor channel thickness in field-effect transistors is a universal phenomenon that has been studied extensively for various families of materials.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] For instance, it has previously been shown that thin-film transistors (TFTs) based on different semiconductor materials exhibit a universal trait: the charge carrier mobility reduces with lowering channel thickness below a critical dimension. [16][17][18][19][20][21][22][23] This phenomenon applies to numerous established technologies including silicongermanium transistors, [16] GaAs/AlGaAs quantum wells, [17] as well as emerging semiconductor technologies including 2D materials (e.g., MoS 2 ), [18] organic semiconductors, [19][20][21] and metal oxide semiconductors. [22][23][24] Traditionally, the The dependence of charge carrier mobility on semiconductor channel thickness in field-effect transistors is a universal phenomenon that has been studied extensively for various families of materials.…”
Section: Introductionmentioning
confidence: 99%
“…In both organic and inorganic materials, the energetic distribution of trap states is typically approximated by a Gaussian function with a standard energetic deviation or an exponential function with a modified characteristic temperature 11,18,20,25,26 . The Gaussian function is a better choice to describe the limited nature of trap density.…”
Section: Modelingmentioning
confidence: 99%
“…The practical OSCs film thickness in the device is generally in the range of smaller than 100 nm. Considering the value of carrier mobility has a dependence on the thickness, the data from the TOF have a large limit on the practical device. And, in addition, for some dispersive materials, the turning point for the curve of photocurrent ∼ time is not obvious, which leads to the failure of the determining of the carrier mobility .…”
Section: Introductionmentioning
confidence: 99%
“…And, in addition, for some dispersive materials, the turning point for the curve of photocurrent ∼ time is not obvious, which leads to the failure of the determining of the carrier mobility . In order to overcome such problems of TOF method, the impedance spectroscopy (IS) method, which uses the suitable mathematical equation, slowly becomes another option. Taking advantage of the traditional IS method, our group has incorporated the particle swarm optimization (PSO) algorithm to overcome some basic fitting problems, and then carried out some research on the interface trap free energy, defect state, and bipolar transport of OSCs. ,, Lots of experimental data have proved that the IS method can easily determine the carrier mobility of dispersive materials (such as in polymer semiconductors) in greatly thicker film (such as 50 nm) in the diode structure …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation